"All sturm and no drang" : Beckett and romanticism : Beckett at Reading 2006 - Hulle, Dirk van; Nixon, Mark (Samuel Beckett today/aujourd'hui ;, 2007)
This new issue of Samuel Beckett Today / Aujourd?hui contains three sections: Beckett and Romanticism, the conference proceedings of Beckett at Reading 2006, and finally a collection of miscellaneous essays. In the past few decades there have been scattered efforts to address the topic of Beckett and Romanticism, but it remains difficult to fathom his ambiguous and somewhat paradoxical attitude toward this period in literature, music and art history. Although far from being a comprehensive examination, the dossier on?Beckett and Romanticism? represents the first sustained attempt to give an impetus to the study of this complex theme. Presented here are contributions on Beckett?s attitudes toward Romantic aesthetics in general, including notions such as the sublime, irony, failure, ruins, fragments, fancy, imagination, epitaphs, translation, unreachable horizons, the infinite, the infinitesimal and the unfinished, but also on Beckett?s reading about the Romantic period, his affinity with specific Romantic artists and their influence on works such as Murphy, the trilogy, Krapp?s Last Tape and All Strange Away. The second part of the current issue presents a selection of papers given at the Beckett at Reading 2006 conference in Reading, organised by the Beckett International Foundation to honour the writer?s centenary. Reflecting the importance of the Beckett Foundation?s Archive to scholars, many of these essays present new empirical research in the field of manuscript studies. Further areas of research are illuminated by other contributions which, together with the essays contained in the 'Free Space? section, show the importance and benefits of scholarly dialogue and cross-fertilization between different approaches in current Beckett Studies.